"FAT" BODIES AND LOW-INCOME: EXPERIENCES AND PERCEPTIONS OF MOTHERS FROM SANTOS, BRAZIL - Priscila de Morais Sato; Gabriela Milhassi Vedovato; Kate Perepezko; Ramiro Fernandez Unsain; Mariana Dimitrov Ulian; Fernanda Baeza Scagliusi (Universidade do Estado do Rio de Janeiro, 2016)
The present study aimed to investigate body image among over-weight, low-income women, using their stories and life experiences to explore, describe and understand how they interpreted their body image and their weight gain process. We performed exploratory qualitative research using in-depth interviews with21 low-income women living in three different urban areas. Through content analysis we identified five aspects of the participants' body image: identity, body experiences, causes of weight gain, ways to lose weight, and body changes. The participants described their bodies in several different ways, such as fat, chubby and strong instead of clinical classifications. Most participants presented a "fat identity", which was mainly based in concrete, functional aspects of the body, rather than an aesthetic image. Difficulties in losing weight through nutritional guidance and feeling discriminated by health professionals were important barriers to engaging with the nutritionist. Our findings underscore the necessity for culturally appropriate weight-loss interventions in low-income female populations. DOI: 10.12957/demetra.2016.22492